Perilaku Budaya Komunitas dalam Arsitektur Rumah Jawa di Pereng, Mojogedang, Karanganyar - Silvia Taliaturrosidah; Agus Purwantoro; Shinta Dwi Astuti; Ari Kurniawan; If Bambang Sulistyono (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to examine the interrelation between Javanese house architecture, local culture, and the social behavior of the community in Pereng Village, Mojogedang, Karanganyar. The focus lies in understanding how architectural forms reflect cultural values and how residents interpret and utilize spaces within and around their homes. Employing a qualitative approach through direct observation and in-depth interviews, the research utilized semi-structured interview guides as instruments, with data analyzed using thematic analysis techniques. The findings reveal that although traditional architectural forms such as joglo and limasan are rarely found, cultural values are still preserved through spatial usage, social practices like communal work (gotong royong), and visual elements such as wayang figures on rooftops. Houses function not only as dwellings but also as social and cultural spaces that embody the collective identity of the Pereng community